An Analysis of the Procurement Business Process in the Supply Management Department of PT Pamapersada Nusantara - Maharani, Jihan Fadila; Nursyamsiah, Siti (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study analyzes the procurement business process within the Supply Management Department of PT Pamapersada Nusantara (PAMA) as a strategic function supporting supply chain effectiveness and operational sustainability. The research employs a qualitative descriptive approach through direct observation during an internship, in-depth interviews with internal stakeholders, and document analysis, including supplier evaluation reports and procurement monitoring results. The analysis covers process mapping, system effectiveness, and supplier performance evaluation using weighted indicators such as delivery time, on-time supply, overdue, discrepancy, and quality, which are compiled into a final score for supplier categorization. Findings reveal that the procurement process is supported by an integrated ERP system (SAP), yet several issues remain, including manual approval delays, late deliveries from certain suppliers, and limited automation in warehouse stock monitoring that reduces real-time visibility. Comparative assessment of two main suppliers, PT Paradhiya Ista and PT Wahana, shows significant performance gaps, with PT Paradhiya Ista achieving 95 percent on-time delivery, while PT Wahana faces discrepancy and overdue challenges. Root cause analysis identifies key inefficiencies stemming from weak interdepartmental integration, poor communication, and a lack of data-driven evaluations. The study recommends improvements to enhance efficiency, effectiveness, and reliability in procurement operations.